(untitled) (Global Journal of Science Frontier Research, 2012)
In this work we present a 3D modeling of the magnetic field influence on electrical model and electrical parameters (J ph , V ph , R s , R sh , C) of a polycrystalline silicon solar cell under intense multispectral illumination. For intense light, the electric field in the base of the solar cell has to be considered; taking into account this electric field and the applied magnetic field in our model lead to two major things: Firstly, new analytical expressions of the continuity equation, the photocurrent and the photovoltage are proposed; secondly an equivalent electrical model of the solar cell under constant magnetic field is proposed and the influence of the magnetic field is pointed out on electrical parameters such as shunt and series resistances and space charge capacitance.